Bacterial infections in pediatric hematopoietic stem cell transplantation recipients: incidence, epidemiology, and spectrum of pathogens: report of the Polish Pediatric Group for Hematopoietic Stem Cell Transplantation. Issue 5 (23rd September 2016) - Zając‐Spychała, O.; Wachowiak, J.; Pieczonka, A.; Siewiera, K.; Frączkiewicz, J.; Kałwak, K.; Gorczyńska, E.; Chybicka, A.; Czyżewski, K.; Jachna‐Sawicka, K.; Wysocki, M.; Klepacka, J.; et al.
Abstract: Background: Infectious complications are a significant cause of hematopoietic stem cell transplantation (HSCT) failure, especially allogeneic HSCT (allo‐HSCT) because of delayed immune reconstitution and graft‐versus‐host disease (GVHD) occurrence. Identifying the factors responsible for bacterial infections (BI) in patients undergoing HSCT will provide much more effective empirical antimicrobial treatment in this group of patients. Objective: The aim of this study was to evaluate the epidemiology and profile of BI in patients after HSCT in 5 centers of the Polish Pediatric Group for Hematopoietic Stem Cell Transplantation in 2012–2013. Patients and methods: In 308 HSCT recipients, we retrospectively analyzed 273 episodes of BI in 113 (36.7%) children aged 0.02–22 years (median age: 7 years), 92 after allo‐HSCT and 22 after autologous HSCT (auto‐HSCT). We assessed incidence of BI in different HSCT types by calculating the Index of Bacterial Infection (IBI) as a ratio of patients with at least 1 BI to all patients who underwent this type of HSCT in the analyzed period. We assessed the profile of BI with particular emphasis on multidrug‐resistant organisms, and impact of underlying disease and of graft‐versus‐host disease on BI episodes. Results: In the studied group, 273 episodes of BI were diagnosed, including 237 episodes after allo‐HSCT and 36 after auto‐HSCT. Among allo‐HSCT recipients diagnosed with at least 1 BI, the IBI was 0.4 (matched sibling donor‐HSCT 0.3; matched donor‐HSCT 0.4; mismatched unrelated donor [MMUD]‐HSCT 0.8; P = 0.027) and after auto‐HSCT 0.3 per 1 transplanted patient. In patient after allo‐HSCT because of myelo‐ or lymphoproliferative diseases and bone marrow failures, the major cause of infections was Enterobacteriaceae, while gram‐positive bacteria predominated in the group with primary immunodeficiencies. In all patients after auto‐HSCT, the dominant pathogen of BI were Enterobacteriaceae ( P = 0.011). Time from each type of HSCT to infection caused by different pathogens did not differ significantly. Conclusions: The risk of BI does not depend on the underlying disease, but only on HSCT donor type and is the highest after MMUD‐HSCT procedure. The profile of BI depends on the underlying disease and HSCT donor type, but does not depend on the occurrence of acute GVHD. Gram‐negative bacteria predominated in patients with myelo‐ and lymphoproliferative diseases, while in patients with primary immunodeficiencies gram‐positive strains were predominant.